Peningkatan Kapasitas Life Skill Pada Program Kewirausahaan Siswa SMK Pelita IV dan Kelurahan Tanjung Duren Utara - Saparso, Saparso; Tecoalu, Melitina; Siswanto, Bambang; Tarigan, Krisnawati; Widjaja, Daniel; Amelinda, Rita; Riruma, Olfien; TJ, Hery Winoto (Jurnal Pengabdian kepada Masyarakat UBJ, 2021)
Empowerment is the development of self-potential in meeting their own economic needs without the help of others. This is done with an entrepreneurship workshop to open the participants' horizons so that they have the same mindset about entrepreneurship. Through this workshop, the participants opened their horizons about the business opportunities around them. The community service carried out aims to develop the economic potential of the existing community and improve community skills and students have the drive and ability to create jobs for themselves and for the surrounding community. With several approaches in the implementation of abmas, it is intended that the participants are easy to accept and implement them in the community so that the target can be achieved in order to have skills and create new jobs as expected.